Cádmio em Latossolo Vermelho cultivado com milho em colunas: mobilidade e biodisponibilidade - Juliatti, M. A.; Prado, R. M. [UNESP]; Barriquelo, M. F.; Lenzi, E. (Sociedade Brasileira de Ciência do Solo, 2002)
Cadmium dynamics in the soil-plant system were evaluated in an experiment with a Typic Hapludox (320 g kg-1 of clay) PVC columns (diameter 0.10 m, height 0.80 m) were filled with soil samples (V % elevated to 70), and the surface layer (0-0.2 m) supplemented with Cd-contaminated biosolid (sewage sludge, pH 6). The biosolid treatments were contaminated as follows (in mg kg-1): 0 (control) 2,500 of Cd, 5,000 of Cd, 2,500 of Cd + 2,500 of Pb, and 5,000 of Cd + 5,000 of Pb. The soil columns were cultivated with maize for a period of 80 days. The total Cd concentrations in the soil samples and maize shoots were determined using nitro-perchloric extraction solution. There was no percolation of Cd into the soil column, so the high amounts of cadmium remained in the surface layer. The concentration of 12 mg kg-1 of Cd in the maize shoots was not enough to cause visible toxicity symptoms in the plants. Pb, applied together with Cd, did not affect the soil-plant system.

Com vistas em avaliar a dinâmica do cádmio no sistema solo-planta, instalou-se um experimento em colunas de PVC (0,10 m de diâmetro e 0,80 m de altura), preenchidas com amostras de Latossolo Vermelho distrófico típico com 320 g kg-1 de argila (elevou-se V % a 70) onde se aplicou biossólido (pH 6) contaminado com Cd, incorporado na camada de 0-0,2 m da coluna. Os tratamentos com biossólido contaminado com cádmio foram (mg kg-1): 0 (testemunha), 2.500 e 5.000 de Cd e dois adicionais (2.500 Cd + 2.500 Pb e 5.000 Cd + 5.000 Pb). Cultivou-se milho nas colunas por um período de 80 dias. As concentrações de Cd nas amostras de solo e na parte aérea do milho foram determinadas em extrato nitro-perclórico. A alta concentração do Cd no solo restringiu-se apenas à camada de incorporação, não havendo lixiviação do elemento na coluna do solo. A concentração de 12 mg kg-1 de Cd não foi suficiente para provocar sintomas visuais de fitotoxidez de Cd em milho. O Pb adicionado juntamente com o Cd não apresentou interferência no sistema solo-planta.
Cadmium in Typic Hapludox columns cultivated with maize: mobility and bioavailability
Keywords: lodo de esgoto; lixiviação; toxidez; Pb; sewage sludge; leaching; toxicity; Pb